Religion, Constitution, and Human Rights: An Overview of Muslim Life and Religious Freedom in the United States - Suci Ramadhan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The United States Constitution affirms that religious freedom is a fundamental human right regardless of religion. It is upheld by every citizen and the country. However, the political policies in a particular country are often considered to paralyze fundamental rights in religion, causing various problems in Muslim life at the social and political levels. This research aims to analyze the intersectional dynamic of religion, constitution, and Muslim human rights towards life and religious freedom in the United States. This qualitative research uses the lens of political approach. Primary data are taken from the United States Constitution and policies, and supported by secondary data from various books, scientific articles, and news. The results suggest that religious sentiment (Islam) is found in the political policies of the United States. Currently, unconstitutional and discriminative policies are gradually removed because it triggers the social and political chaos. The United States constitution strives towards a pluralist and multi-religious country rebuilding that is safe and peaceful for religion as guaranteed by the constitution. In fact, the public and political spaces have been occupied by many Muslims in an effort to resolve the problems of state and human rights, including the religious sentiment issues.